Blood Transfusions in Dogs and Cats: Blood Typing, Cross Matching - Branquinho, T. (2013)
The blood transfusion (administration of blood) is a resource of veterinary medicine with several indications. Point-of-care blood-typing methods, including both typing cards and rapid gel agglutination, are readily available. Following blood typing, cross matching is performed on one or more donor units of appropriate blood type. Cross matching reduces the risk of transfusion reactions but does not completely eliminate the risk of other types of transfusion reactions in veterinary patients. All transfusion reactions should be appropriately documented and investigated. It is, therefore, important to have in-depth technical knowledge about concepts and procedures involved in clinical blood transfusion, so that the entire procedure can be performed in the most appropriate way and with a high success rate.